2020
DOI: 10.3389/fvets.2020.00524
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Perceptions of Preventing Antibiotic Resistance on Sheep and Beef Farms: Risk, Responsibility, and Action

Abstract: Antibiotic resistance is one of the most serious public health risks facing humanity. The overuse of antibiotics in the treatment of infectious disease have been identified as sources of the global threat of antibiotic resistance. This paper examines how farmers perceive and manage risks associated with overuse of antibiotics. Specifically, the paper examines the role of habitus and risk in determining farmers' decisions to adopt national antibiotic reduction targets set by members of the Responsible Use of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Beef and sheep producers have some of the lowest levels of use among the UK livestock sectors ( 36 ), but are still subject to pressure to minimise use where possible. Preventive antibiotic use was uncommon in neonatal calves in the experience of the participants, but neonatal loss has been identified as “hotspot” for antibiotic use in sheep ( 22 ). Oral antibiotics are used widely to prevent and treat bacterial gastrointestinal infections (“watery mouth”) in lambs, and were the main subject of the discussions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beef and sheep producers have some of the lowest levels of use among the UK livestock sectors ( 36 ), but are still subject to pressure to minimise use where possible. Preventive antibiotic use was uncommon in neonatal calves in the experience of the participants, but neonatal loss has been identified as “hotspot” for antibiotic use in sheep ( 22 ). Oral antibiotics are used widely to prevent and treat bacterial gastrointestinal infections (“watery mouth”) in lambs, and were the main subject of the discussions.…”
Section: Resultsmentioning
confidence: 99%
“…This can be a source of job dissatisfaction for vets working with farm animals, contributing to farm vets pursuing other career paths and consequent workforce issues in rural veterinary practice ( 21 ). Low veterinary involvement on beef and sheep farms has been identified as a key challenge in achieving reductions in antibiotic use, with neonatal loss as one of the major drivers of high antibiotic use ( 22 ). The farm business income from grazing livestock enterprises in the UK is significantly lower than all other livestock production sectors ( 23 ), which may restrict the resources available to invest in veterinary input.…”
Section: Introductionmentioning
confidence: 99%
“…They were more eager to describe their daily efforts to keep their animals healthy, possibly reflecting policy efforts to focus on preventive animal health work. Farmers in other countries in Europe and the US acknowledge the need for reducing antibiotic use, but some believe in the necessity of antibiotics for a good profit in animal production ( 25 , 30 , 31 ). To change farmers' perceptions and practices, it has been suggested that veterinarians could play a role as sources of information and to facilitate learning processes ( 25 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study informants highlighted the close network of farmers and veterinarians and said this was a facilitating factor. The opposite situation was described among sheep and beef farmers in the UK who reported taking decisions themselves regarding when to treat their animals with antibiotics ( 31 ). Industry veterinarians in the present study seemed to play a role as a link between veterinary authorities and the farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the important responsibility of food animal producers to reduce antibiotic use in animal agriculture, little or vague understanding exists regarding antibiotics use and antibiotics resistance, and recent regional, national, and international regulations to address the challenges associated with AMR have not been perceived well. As an instance, many food animal producers are either not aware or slightly aware of the VFD statement in the US or other similar national rules in other countries, and some of the farmers are perceived these regulations as not useful [ 49 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. More awareness regarding the VFD or other similar plans in other countries and understanding the impact of AMR are needed among agricultural animal producers.…”
Section: Perception Of Regulations Regarding the Use Of Antimicrobmentioning
confidence: 99%